Implementasi Teknologi Filtrasi Pada Sistem Pengolahan Air Minum Sebagai Upaya Pemenuhan Air Bersih dan Sanitasi Masyarakat - Lailatul Qomariyah; Daril Ridho Zuchrillah; Agus Surono; Rizaldi Hakim Ash Shiddieqy; Muhammad Lukman Hakim; Danawati Hari Prajitno; Iis Dewi Ratih; Fausania Hibatullah; Mochammad Reza Habibi; Gatot Kusrahardjo (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Rapid population growth causes an increase in clean water, where water is the main need for humans and living creatures. The availability of water in the world is very abundant, but only a few percent can be used or consumed. The provision of clean water often encounters problems resulting in obstacles in providing clean water for the community. The people of Tanjungsari Hamlet are one of the communities who are having problems getting clean water because the well water they use contains quite high levels of iron (Fe). Therefore, the ITS community service team and KKN students created a filtration technology implementation program to help provide clean water for the residents of Dsn.Tanjungsari. Starting from planning program implementation, conducting site surveys and identifying problems, continuing with designing and working on tools/technology, then installing tools/technology at Dsn.Tanjungsari and finally monitoring the performance of tools/technology after the tools/technology are installed. The results obtained are that the technology applied can eliminate strong odors and make water free from Fe content and the equipment used to distribute clean water uses reservoirs which originally had a capacity of 3,000 liters to a capacity of 8,300 liters.